Краєзнавчий рух на Уманщині в 1990-ті роки: досвід, проблеми - Лісовська, О.; Скус, О. (Краєзнавство, 2024)
У статті, на основі опрацювання широкого кола джерел та літератури, досліджується розвиток краєзнавства на Уманщині в роки незалежності України. З’ясовуються форми та методи краєзнавчої роботи, розкривається внесок у дослідження історії краю краєзнавців-аматорів та науковців, узагальнюється набутий досвід. Автори приходять до висновку, що краєзнавство на Уманщині у 1990-х роках розвивалося на основі тісного поєднання його наукових і громадських форм. В утвердженні сучасних наукових засад дослідження регіональної історії, провідну роль взяли на себе науковці вищих навчальних закладів, музеї та бібліотеки, заклади освіти. Важливу роль у координації краєзнавчої роботи відігравала Уманська організація Національної спілки краєзнавців України. Розвиток краєзнавства на Уманщині в 1990-х роках характеризувався урізноманітненням напрямків та форм дослідницько-пошукової роботи і сформував основу подальших наукових краєзнавчих досліджень краю в ХХІ столітті. The article, based on the study of a wide range of sources and literature, examines the development of local history in the Uman Oblast during the years of Ukraine's independence. The forms and methods of local history work are clarified, the contribution of amateur local historians and scientists to the study of the history of the region is revealed, and the acquired experience is summarized. The authors come to the conclusion that local history in the Uman region in the 1990s developed on the basis of a close combination of its scientific and public forms. In the establishment of modern scientific foundations of regional history research, scientists of higher educational institutions, museums and libraries, and educational institutions took the leading role. An important role in the coordination of local history work was played by the Uman Organization of the National Union of Local History of Ukraine. The development of local history in the Uman Region in the 1990s was characterized by the diversification of directions and forms of research work and formed the basis of further scientific local history studies of the region in the 21st century.